Serotype Distribution and Antimicrobial Susceptibility of Streptococcus pneumoniae in Pre- and Post- PCV7/13 Eras, Taiwan, 2002–2018 - Wu, Chi-Jung; Lai, Jui-Fen; Huang, I-Wen; Shiau, Yih-Ru; Wang, Hui-Ying; Lauderdale, Tsai-Ling (Frontiers in Microbiology, 2020)
In Taiwan, the 7-valent pneumococcal conjugate vaccine (PCV7) was introduced in 2006 and a PCV13 national childhood catchup program was implemented in 2013. To delineate the trend of serotype distribution and antimicrobial susceptibility following vaccination programs, we investigated a total of 1845 Streptococcus pneumoniae isolates collected biennially between 2002 and 2018 over a 3-month period from 25 hospitals. The number of isolates collected over the years decreased significantly in all age groups, from a total of 320 isolates in 2002 (pre-PCV), to 196 in 2010 (post-PCV7/pre-PCV13), to 89 in 2018 (post-PCV13). Overall, PCV7/PCV13 serotypes comprised 66.9%/76.3%, 53.1%/78.1%, and 15.7%/31.5% of isolates in 2002, 2010, and 2018, respectively. The leading serotypes in the pre-PCV era were 23F, 19F, 6B, and 14, while serotype 19A predominated in the post-PCV7/pre-PCV13 era, but non-vaccine serotypes (NVT) 15A (18.0%) and 23A (15.7%) surpassed 19A (10.1%) to become the top two leading serotypes in 2018. All the major serotypes, including the emergent serotypes 15A and 23A, were multidrug-resistant with high rates of non-susceptibility to ß-lactam (except serotype 3) and several non-ß-lactam agents. PFGE and MLST revealed the emergence and spread of meropenem-nonsusceptible serotype 15A-ST63 and serotype 23A-ST166 clones in recent years. We conclude that successive implementation of PCVs has led to a marked decrease in pneumococcal isolate burden, but the replacement by meropenem-nonsusceptible NVT 15A and 23A highlights the need for continued local surveillance to track pneumococcal evolution in each region to help vaccine poly-valency decisions.